(untitled) (Research, Society and Development, 2020)
Defined as the inability of the kidneys to perform their basic functions, Chronic Kidney Failure (CKF) is an important cause of morbidity and mortality worldwide. The objective of the present study was to evaluate the epidemiological profile of patients hospitalized with CKF, in the State of Amazonas, during the period from 2015 to 2019. It is characterized by being a quantitative, retrospective, ecological type study. Data were collected from information derived from SIH / DATASUS. The following epidemiological variables were analyzed: number of hospitalizations, gender, ethnicity, age group and number of deaths. The study identified an increasing number of hospitalizations for CKF in the 5 years analyzed, being 766, 881, 910, 1351 and 1657 in the years 2015, 2016, 2017, 2018 and 2019, respectively. The male gender was the most affected, with 56% of hospitalizations and the most prevalent color was brown, responsible for 82.03% of cases. Most patients were 50 years old or older. There was an annual increase in the number of deaths due to CKF in the analyzed period. The year with the highest number of deaths was 2019, with a total of 244 deaths. Therefore, it is essential to expand access to treatment for patients with CKF, especially those who live in the most remote locations of large urban centers in the northern region, in order to improve disease control, prevent complications and, consequently, reduce morbidity and mortality associated with CKF.